2022
DOI: 10.1097/rlu.0000000000004143
|View full text |Cite
|
Sign up to set email alerts
|

A 68Ga-FAPI-46 PET/CT Imaging Pitfall in Assessing Residual Gastric Cancer Early After Chemotherapy

Abstract: After neoadjuvant chemotherapy, preoperative imaging with 68Ga-FAPI-46 PET/CT showed a similar level of tracer uptake at the location of the primary tumors in 2 patients with gastric cancer. Postoperative histopathology revealed residual malignant cells only in one of the patients, whereas the elevated FAPI uptake in the other patient correlated to an inflammatory reaction and fibrosis. With this case, we would like to highlight that an increased FAPI uptake in inflammatory and fibrotic tissue early after chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Kang et al previously reported 96.1% (25/26) of anastomotic sinuses and fistulas that exhibited increased FDG uptake in patients who underwent rectal cancer surgery [30]. Furthermore, Buren et al recently described a case where an abnormal 68 Ga-FAPI-04 uptake lesion was proven to be fibrosis induced by neoadjuvant chemotherapy [31]. In addition, multiple rounds of injury to an anastomosis site leading to inflammation intertwined with fibrosis repair might partly explain the results observed with FAPI + /FDG + PET imaging in non-anastomotic recurrent patients.…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al previously reported 96.1% (25/26) of anastomotic sinuses and fistulas that exhibited increased FDG uptake in patients who underwent rectal cancer surgery [30]. Furthermore, Buren et al recently described a case where an abnormal 68 Ga-FAPI-04 uptake lesion was proven to be fibrosis induced by neoadjuvant chemotherapy [31]. In addition, multiple rounds of injury to an anastomosis site leading to inflammation intertwined with fibrosis repair might partly explain the results observed with FAPI + /FDG + PET imaging in non-anastomotic recurrent patients.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced gastric cancer patients who fail to respond to firstline therapy face a high risk of relapse, progression, and ultimately, increased mortality rates [9]. In such cases, person-alized second-line treatments are administered based on prior clinical practice and patient tolerance.…”
Section: Discussionmentioning
confidence: 99%